Magnetic Properties and Mössbauer spectroscopy of NdFe1-xMnxO3. (18th March 2015) - Lazurova, J; Mihalik, M; jr, M Mihalik; Vavra, M; Zentkova, M; Briancin, J; Perovic, M; Kusigerski, V; Schneeweiss, O; Roupcova, P; Kamenev, K V; Misek, M; et al.
Abstract: The effect of particle reduction to nanoscale size and substitution of Mn 3+ ions for Fe 3+ ions on the crystal structure, lattice dynamics, Mössbauer spectra and magnetic properties in NdFe1-x Mnx O3 compounds have been studied. X-ray powder diffraction and Raman spectroscopy revealed that the Jahn-Teller distortion of lattice dominates for samples with x > 0.4. The average particle size of NdFeO3 nanoparticles (NAP) increases with annealing at 600°C from about 15 nm to 25 nm. The presence of superparamagnetic particles was indicated by Mössbauer measurements in NdFeO3 NAP system. Sextets in NdFe1-x Mnx O3 Mössbauer spectra can be modelled with several local environments of Fe 3+ induced by substitution. The reduction of dimensionality and the substitution induce a decrease of the Néel temperature T N1 from 691 K to 544 K for NAP or to 356 K for x = 0.4, however the temperature of spin reorientation T SR increases with substitution. The saturated magnetization obtained at 1.9 K increases and ferromagnetic component is removed below T SR with the substitution.